The evaluation of wastewaters from an oil sand extraction plant ... - Strosher, M. T.; Peake, E. (University of Alberta Library, 1976)
Organic constituents of wastewaters from the existing Athabasca oil sands extraction plant were characterized and quantified. Twenty-one chemical parameters were determined on a total of ten samples taken during November and December, 1975 from the tailings pond dike filter drainage system, the upgrading plant final effluent to the Athabasca River and the intake pond waters. In addition, a number of specific aromatic hydrocarbons and organic sulphur compounds were identified and heavy metals and vanadium were determined. Tailings pond dike filter drainage samples contained 100-120 mg/l of total organic carbon, 69% of which was extractable with organic solvents. Ninety-two percent of the extractable carbon was in the form of oxygenated compounds, including organic acids (79%), phenols (4.5%), ketones (2.7%), aldehydes (1.9%), organic acid esters (1.5%), amides (1.0%), and quinones (0.2%). Organic sulphur compounds averaged 5.3%, organic nitrogen compounds 1.1% and hydrocarbons 0.04% of the extractable ...